Effect of Functional diversity on Software Performance - Viswanatha Rao, Balajee (2011)
For the past few decades, there has been numerous literature produced on functional diversity and performance. However, the relationship between functional diversity and performance in software industry is clearly not explained and results are found to be inconsistent. The main focus of this research is to explore the effects of functional diversity on software project performance by conducting a qualitative study. Four metrics were chosen from literature namely decision making, creativity and innovation, problem solving, learning which was observed against functional heterogeneity. A total of three semi- structured interviews were conducted which accounts for interviewees’ perspectives and views on the topic. The research clearly explains that all the chosen metrics play an active role in influencing the performance of a software team positively provided if the team is headed by an experienced leader. Suitable implications for future research and managers are also discussed in the study.